2019
DOI: 10.1021/acs.oprd.9b00161
|View full text |Cite
|
Sign up to set email alerts
|

The 25th Anniversary of the Buchwald–Hartwig Amination: Development, Applications, and Outlook

Abstract: The palladium-catalyzed cross-coupling of amines and aryl (pseudo)halides, now commonly known as the Buchwald−Hartwig amination, was first reported 25 years ago. Since the simultaneous breakthrough reports of Buchwald and Hartwig in 1995, this reaction has transformed the way synthetic chemists think about synthesizing aromatic amines. In this highlight article, a short showcasing discussion about the genesis of this reaction is provided, along with selected examples showing the impact of this transformation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
150
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(160 citation statements)
references
References 48 publications
0
150
0
Order By: Relevance
“…Tin‐free palladium‐catalyzed C−N cross‐couplings by Buchwald and Hartwig in 1995 and copper‐catalyzed aminations by Buchwald and Goodbrand in 1999 accelerated industrial applications of C−N bond‐forming reactions . Pfizer synthesized the CETP inhibitor torcetrapib by employing an amination reaction (Scheme a) .…”
Section: Transformations In Green Solventsmentioning
confidence: 99%
“…Tin‐free palladium‐catalyzed C−N cross‐couplings by Buchwald and Hartwig in 1995 and copper‐catalyzed aminations by Buchwald and Goodbrand in 1999 accelerated industrial applications of C−N bond‐forming reactions . Pfizer synthesized the CETP inhibitor torcetrapib by employing an amination reaction (Scheme a) .…”
Section: Transformations In Green Solventsmentioning
confidence: 99%
“…[32,57] The difficulty of CÀ O reductive elimination is the cause of the lesser degree of development attained by palladiumcatalyzed coupling of aryls and alcohols to ethers [13,58] in contrast with the analogous CÀ N coupling in Buchwald-Hartwig aryl amination. [12] On the contrary, β-hydrogen elimination is relatively frequent for alkoxides and constitutes the basis for a number of catalytic applications mentioned in the Introduction. [17][18][19][20] Mechanistic studies have shown that βhydrogen elimination may, in fact, involve different pathways, summarized in Scheme 10.…”
Section: Methodsmentioning
confidence: 99%
“…[11] The number of applications of the special "organometallic-like" reactivity of transition metal compounds with MÀ N or MÀ O bonds has experienced a continuous growth. Some prominent examples of these are the Buchwald-Hartwig aryl amination [12] (now celebrating its 25th anniversary) and the analogous etherification reaction, [13] the Suzuki-Miyaura reaction, [14] reductive couplings of carbonyl and unsaturated compounds, [15] reduction of carbonyl compounds, [16] aerobic [17] or acceptorless [18] alcohol oxidation, hydrogen borrowing alkylation, [19] or various dehydrogenative coupling reactions, [20] just to cite a few of them (see Chart 1). In parallel, an intense effort has been deployed to understand the fundamental aspects of reactive metal-heteroatom bonds, either as catalytic intermediates or as stoichiometric reagents.…”
Section: Introductionmentioning
confidence: 99%
“…One frequently used Pdcatalysed transformation yet to be combined with biocatalysis is the Buchwald-Hartwig cross-coupling (BHA), which couples nucleophilic amines and aryl halides to afford anilines. [38][39][40][41] Herein we present a chemoenzymatic approach to chiral N-arylamines, combining a variety of enantioselective biocatalytic transformations with a surfactant-enabled BHA (Scheme 1). [11,40,42] We initially envisaged a one-pot process involving conversion of the substrate (ketone/imine/alcohol) followed by in situ BHA in an aqueous environment without any intermediate workup.…”
Section: N-arylamines Are An Important Structural Motif Present Inmentioning
confidence: 99%